Planificación Fiscal Agresiva, el nuevo paradigma de la norma de precios de transferencia y la elusión en el Código Tributario - Villanueva Gutiérrez, Walker (2017)
In this paper, the author analyzes the problematic of the aggressive tax planning, due to the lack of coherence between the tax rules of the different States and indicates the way in which the transfer pricing rule should be applied. Also, he analyzes the regulation of the anti-avoidance provision in the Tax Code and criticizes how the Supreme Court applies this anti-avoidance provision and the reasoning of the Tax Court to derive legal effects based on the economic content.